Why does aging anxiety emerge? A study on the influence of socioeconomic status - Yang, Shuchao; Ge, Daoshun (Frontiers in Psychology, 2025)
Aging anxiety constitutes a pressing practical issue impacting active aging and healthy aging of the population. Existing theories on aging anxiety predominantly analyze its intrinsic causes through psychosocial perspectives such as perception and identity formation, yet insufficient attention has been paid to structural factors like socioeconomic status that may influence aging anxiety. Current research findings regarding the impact of socioeconomic status on aging anxiety exhibit inconsistencies, while the analysis of underlying mechanisms requires further refinement. This study integrates the Fundamental Causes Theory of health and the Stress Process Theory, utilizing data from the Chinese General Social Survey (CGSS) to investigate the mechanisms through which socioeconomic status affects aging anxiety. The research reveals that socioeconomic status influences individual aging anxiety both directly and indirectly through mediating mechanisms involving anxiety stressors and perceptions of aging. Specifically, improvements in objective socioeconomic status indicators (education and income) and positive expectations regarding subjective socioeconomic status significantly alleviate aging anxiety. Higher educational attainment and income levels reduce individuals’ probability of encountering practical and anticipatory aging-related stressors such as illness and caregiving needs, while fostering more positive perceptions of aging, thereby diminishing aging anxiety. The influence of socioeconomic status on aging anxiety is moderated by regional urbanization levels and urban–rural structures. The anxiety-reducing effect of educational attainment strengthens in regions with higher urbanization levels. Rural residents experience stronger aging anxiety than urban residents, and increased participation in social insurance can effectively alleviate this anxiety among rural residents. This study provides valuable references for cultural interventions and policy-making aimed at alleviating aging anxiety.